2015
DOI: 10.1007/s13197-014-1694-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of spices and lactic acid bacteria as antimicrobial agent to extend the shelf life of metata ayib (traditional Ethiopian spiced fermented cottage cheese)

Abstract: Spices and lactic acid bacteria have natural antimicrobial substances and organic compounds having antagonistic activity against microorganisms. The objective of this study was to investigate the role of spices and lactic acid bacteria as antimicrobial agent to extend the shelf life of metata ayib. Antimicrobial activities of spices and lactic acid bacteria (LAB) filtrates were determined by agar well diffusion method against E. coli, S. aureus, S. flexneri and S. peumoniae. Aantimicrobial activity of garlic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Additionally, the results of PCA analysis showed that the extract of clove (both fruit and flower) and cinnamon were spotlighted as potential good candidates as natural food preservatives due to their excellent antibacterial and antioxidant properties. Several other spice extracts like coriander, cinnamon, oregano, mustard, holy basil, and green pepper were also reported to be potent food preservatives [40,41,42,43,44]. Indeed, some studies demonstrated the potential application of clove extracts in raw chicken meat and raw pork during storage to extend shelf-life, in terms of reducing microbes, maintaining natural color, and retarding lipid oxidation [40].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the results of PCA analysis showed that the extract of clove (both fruit and flower) and cinnamon were spotlighted as potential good candidates as natural food preservatives due to their excellent antibacterial and antioxidant properties. Several other spice extracts like coriander, cinnamon, oregano, mustard, holy basil, and green pepper were also reported to be potent food preservatives [40,41,42,43,44]. Indeed, some studies demonstrated the potential application of clove extracts in raw chicken meat and raw pork during storage to extend shelf-life, in terms of reducing microbes, maintaining natural color, and retarding lipid oxidation [40].…”
Section: Discussionmentioning
confidence: 99%
“…The various therapeutic effects of spices have been reported which includes antibacterial, antifungal, anti-emetic, anti-ulcer, antiplatelet, anti-pyretic, anti-inflammatory, antioxidant and cytotoxic properties. 24 Various previous studies have also displaying the antibacterial and bactericidal effect of some potent spices and herbs towards various pathogenic bacteria. 3 In this study, we have used three spices cardamom (Elettaria cardamomum), cinnamon (Cinnamomum verum) and fennel (Foeniculum vulgare) extract (CAE, CIE and FEE) for their anti-microbial and cytotoxic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, 2-hydroxybenzoic acid enhanced the biocontrol efficacy of the yeast R. glutinis against P. expansum and A. alternata in cherry fruit [ 207 ] Finally, the role of other ingredients in foods to help extend product shelf-life is also important. The use of spices combined with an antifungal LAB culture to efficiently prevent fungal spoilage of an Ethiopian spiced fermented cottage cheese was recently described [ 208 ].…”
Section: Implementation Of Biopreservation Methods Against Fungal mentioning
confidence: 99%